2018
DOI: 10.1177/1073191118774841
|View full text |Cite
|
Sign up to set email alerts
|

The Compensatory ADHD Behaviors Scale (CABS): Development and Initial Validation

Abstract: Several measures are available that assess inattention, hyperactivity/impulsivity, and executive functioning deficits. Treatments for adults with attention-deficit/hyperactivity disorder (ADHD) and skill-based academic interventions focus on improving compensatory strategies to ameliorate functional impairment; however, no measure exists that examines the compensatory behaviors adults utilize to compensate for the functional deficits associated with inattention and hyperactivity/impulsivity. The current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 82 publications
3
14
0
Order By: Relevance
“…Because of the one-to-one correspondence between the use and effectiveness of CABS, this study, like Dr. P. Castagna’s study, analyzed the use and effectiveness scales in parallel. 24 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the one-to-one correspondence between the use and effectiveness of CABS, this study, like Dr. P. Castagna’s study, analyzed the use and effectiveness scales in parallel. 24 …”
Section: Methodsmentioning
confidence: 99%
“…In 2019, in order to measure the compensatory behaviors in adult ADHD, Castagna et al developed then validated the Compensatory ADHD Behaviors Scale (CABS) in the USA. 24 Currently, there are no studies validating the reliability and validity of the CABS scale in other countries. The CABS contained a variety of organizational planning and behavioral management methods, which could be divided into two major modules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Awareness of an individual’s EF deficits can serve to inform treatment, as clinicians can more specifically tailor therapeutic strategies to best serve a patient’s needs (Barkley, 2014; Mohlman & Gorman, 2005). Additionally, measures of EF are suggested to be some of the most effective measures of adaptive functioning (Chaytor et al, 2006) and have demonstrated good ecological validity in predicting functional impairment (Barkley & Fischer, 2011; Castagna et al, 2019; Chaytor et al, 2006). Given that previous studies have implicated aspects of EF as possible predictors of LOS among individuals deemed IST (A.…”
mentioning
confidence: 99%
“…EF can be assessed using performance-based measures or self-report measures of EF problems in daily life. These self-report measures assess multiple domains of EF in daily life (e.g., organization, time management) and have demonstrated good ecological validity in predicting functional impairment as assessed by self-report, informant-rated, and clinician-rated measures (Barkley & Fischer, 2011; Castagna et al, 2019; Chaytor et al, 2006). Although performance-based and self-report measures are only modestly correlated (Dehili et al, 2017; Toplak et al, 2013), both are used as measures of EF in neuropsychological assessment (Rabin et al, 2016).…”
mentioning
confidence: 99%